2007
DOI: 10.1088/1464-4258/9/9/s31
|View full text |Cite
|
Sign up to set email alerts
|

Accurate modelling of left-handed metamaterials using a finite-difference time-domain method with spatial averaging at the boundaries

Abstract: Abstract. The accuracy of finite-difference time-domain (FDTD) modelling of left-handed metamaterials (LHMs) is dramatically improved by using an averaging technique along the boundaries of LHM slabs. The material frequency dispersion of LHMs is taken into account using auxiliary differential equation (ADE) based dispersive FDTD methods. The dispersive FDTD method with averaged permittivity along the material boundaries is implemented for a two-dimensional (2-D) transverse electric (TE) case. A mismatch betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Thus, the conventional FDTD method cannot correctly simulate materials with the properties of ε r , µ r , ε z , µ z and new dispersive FDTD techniques have to be employed, like in the case of the left-handed metamaterials (LHMs) [37]. The parameters are mapped with dispersive material models and more precisely with the well-known and widely used Drude model:…”
Section: Numerical Modeling Of the Lossy Cloaking Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the conventional FDTD method cannot correctly simulate materials with the properties of ε r , µ r , ε z , µ z and new dispersive FDTD techniques have to be employed, like in the case of the left-handed metamaterials (LHMs) [37]. The parameters are mapped with dispersive material models and more precisely with the well-known and widely used Drude model:…”
Section: Numerical Modeling Of the Lossy Cloaking Structurementioning
confidence: 99%
“…Hence, for the proposed dispersive FDTD method a spatial resolution of ∆x < λ/10 is not sufficient unlike the conventional dielectric material simulations in which it is the required value [36]. From a previous analysis of left-handed metamaterials (LHMs) [37], it was found that spurious resonances are caused due to coarse time discretisation which leads to numerical errors and inaccurate modeling results. It was proposed that a spatial resolution of ∆x < λ/80 is essential for accurate simulations.…”
Section: Numerical Modeling Of the Lossy Cloaking Structurementioning
confidence: 99%
“…In the spatial grid, , , and are collocated with the corresponding field components, as done in [33], as opposed to being at the center of the Yee cell, as done in [31]. As discussed elsewhere [33] and [34], numerical mismatching effects (spurious surface plasmon) that may occur at double-negative interfaces need to be properly addressed. This can be achieved by using either an arithmetic mean of the material permittivity [34] or a current averaging technique [33] at the interfaces.…”
Section: Formulationmentioning
confidence: 99%
“…As discussed elsewhere [33] and [34], numerical mismatching effects (spurious surface plasmon) that may occur at double-negative interfaces need to be properly addressed. This can be achieved by using either an arithmetic mean of the material permittivity [34] or a current averaging technique [33] at the interfaces. In this work, we use the latter technique at the interfaces.…”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation